The Effect of Principal’s Leadership and Organizational Justice on Elementary School Teacher’s Performance - Wistiany, Rahma; Arafat, Yasir; Rahman, Andi (Yayasan Sembilan Pemuda Indonesia, 2024)
Because of a phenomenon he noticed in earlier researchers’ work and the empirical finding that principal leadership and organizational justice affect teacher performance, the author was inspired to conduct this study. To better understand how these two factors affect the performance of State Elementary School (SD) teachers in Cluster 1 Koba District, Central Bangka Regency, Bangka Belitung Islands Province, the author conducted this study. application of quantitative research techniques. 84 instructors from 8 public elementary schools located in Cluster 1 made up the sample, which was determined using random sampling. Koba District. By distributing questionnaires with a Likert scale of 1 to 4, the data were collected. The SPSS-26 program was used to statistically process the data. The outcomes of the data analysis support the finding that organizational justice and the principal’s leadership have a favorable and significant impact on teacher performance, either separately or collectively. According to the coefficient of determination test, organizational fairness and the principal’s leadership had a combined 52.2% effect on teacher performance.